Queer Enough? Homonormativity and Hegemonic Gay Masculinity in Contemporary Biopics - Müller, Anna Carolin (Filmstudien, 2023)
The interrelationship between heteronormativity, homonormativity and hegemonic masculinity has widereaching ramifications for the representation of important moments and agents in LGBTQIAN+ history. In this study, the author examines how the films Howl, Stonewall and Milk enact the emancipation of their protagonists, while simultaneously reproducing their oppression and aestheticising their discrimination, thus making it consumable. This contradiction is emblematic of new forms of exclusion that function more subtly than blatant homophobia, outright sexism or overt racism, while at the same time rejecting a more complex repre-sentation of social experiences but instead solidifying static, definable identities.